Fertility Trends and Population Policy in the Canton of Sarajevo - Reményi Péter; Gekić Haris; Bidžan-Gekić Aida (Tér és Társadalom, 2024)
The demography of Bosnia and Herzegovina fits into the Southeast-European trends with sub-replacement fertility and high emigration rates. At the national level, natural decline started in 2007, while migration is influenced by the war and its aftermath, as well as several economic and political push factors (low wages, corruption, high unemployment, etc.), and also has a serious impact on birth and death rates. On the other hand, demographic trends in the Canton of Sarajevo differ from the national pattern. It reached sub-replacement fertility more than a decade later (2019), and migration still has a positive balance: besides significant emigration rates, immigration to the Canton, especially from the other parts of Bosnia and Herzegovina, is higher. Since migration involves younger generations, it is also a factor behind the more favourable fertility rates, and can be evaluated as a consequence of better socio-economic development in the capital and its gravitational area.